Information Systems Planning in the Not for Profit Sector in Western Australia - Siwale, Maka (Curtin University, 2015)
This research was an exploratory-descriptive study on Information Systems (IS) Planning in not-for-profit organisations (NFPOs) in Western Australia. Much has been written on IS planning in for-profit organisations (FPOs), but little is known about it in the NFPO sector. This research provides insight into IS planning in NFPOs and how it relates to the achievement of their mission or goals. It also identifies the problems of current IS planning practice in NFPOs.